2014
DOI: 10.5812/traumamon.15958
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Infections in ICU Patients without Underlying Disease on Ventilators

Abstract: Background:At present, the use of ventilator support is an important part of treatment in ICU patients. However, aside from its well-known advantages, the use of these devices is also associated with complications, the most important of which is pulmonary infection (PI). PI has a high rate of morbidity and mortality.Objectives:This study aimed to evaluate the prevalence of PI in mechanically-ventilated patients and the role that factors, such as age, sex, and duration of intubation, play in this regard.Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Pulmonary infection, possibly due to a high rate of mechanical ventilation, 14 is the most common and major cause of sepsis in patients in the ICU. Caraballo et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary infection, possibly due to a high rate of mechanical ventilation, 14 is the most common and major cause of sepsis in patients in the ICU. Caraballo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis-related myocardial injury is not only limited to heart tissue, but also affects systemic hemodynamics and has fluid resuscitation effects, 13 which significantly affect the short-term and long-term prognosis of patients. 10 Pulmonary infection, possibly due to a high rate of mechanical ventilation, 14 is the most common and major cause of sepsis in patients in the ICU. Caraballo et al 15 showed a significant correlation between pulmonary infection and hospital mortality in patients with sepsis (OR: 3.4, 95% CI: 2.2-5.5).…”
Section: Discussionmentioning
confidence: 99%
“…For hyperinflammation, immune cells become excessive and hyperactive, producing sustained and large quantities of cytokines that cause elevated circulating levels, leading to systemic immune cell activation and cytokine production (i.e., cytokine storm) 1 . The systemic inflammation can rapidly progress to disseminated intravascular coagulation, endothelium damage, capillary leakage, multiorgan (e.g., liver, kidney, heart, and brain) dysfunction, ARDS, and fatality 11,12 . Although the initial driver may differ, the late-stage clinical features of hyperinflammation and cytokine storm converge.…”
Section: Introductionmentioning
confidence: 99%
“…However, under certain conditions, such as an overwhelming pathogen burden, immune cell activation and cytokine production become dysregulated, excessive, persistent, and systemic (i.e., cytokine storm) 1 . Hyperinflammation can rapidly progress to disseminated intravascular coagulation, vascular leakage, acute respiratory distress syndrome (ARDS), multi-organ dysfunction (MODS), and death 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical ventilation (MV), a basic life support method used during anesthesia, plays a key role in the treatment of critical patients, especially those with acute lung injuries and acute respiratory distress syndrome (Ghanbarpour et al, 2014;Tsushima and Tatsumi, 2014). MV has both positive and negative effects in the field of anesthesia medicine; MV improves the functions of critical organs, including the heart, brain, liver, and kidney, thereby stabilizing the inner environment of the body and facilitating patient recovery.…”
Section: Introductionmentioning
confidence: 99%